Normal semigroups of endomorphisms of proper independence algebras are idempotent generated - Araújo, João (2015)
Let A be a proper independence algebra of finite rank, let G be the group of automorphisms of A, let a be a singular endomorphism and let aG be the semigroup generated by all the elements g°1ag, where g 2 G. The aim of this paper is to prove that aG is a semigroup generated by its own idempotents.